Development of Financial Technology Investment in Indonesia Increasing Public Interest Industrial Revolution 5.0 - Itok Dwi Kurniawan (JHR (Jurnal Hukum Replik), 2022)
The creation of a stable financial system that benefits all levels of society. In this regard, financial institutions play an important role through their intermediary function to promote economic growth, income distribution, poverty alleviation and the achievement of financial system stability. Just industryfinance that is growing very rapidly is not necessarily accompanied by access to finance adequate finance. In fact, access to financial services is a prerequisite. The involvement of the wider community in the economic system is important. The existence of Fintech makes the process of financial transactions more practical and faster. Fintech is now developing all over the world, including Indonesia in the face of the 5.0 industrial revolution.